Evaluation of Early Diagnostic Services for the Elderly. Issue 5717 (1st August 1970) - Lowther, C. P.; MacLeod, R. D. M.; Williamson, J.
Abstract : Medical examination was offered to a group of "high risk" old people who were not necessarily patients or known to their family doctors, but with the agreement of these family doctors. Two clinics set up for this purpose have been running for several years, and the results of examination and follow-up of 300 consecutive patients are reported. Major conditions were found in two-thirds of patients producing functional impairment in most of these. Recommendations as to therapy and management were carried out in 161 of 194 patients but not in the remainder. Clear evidence of improvement was found in half of the patients who carried out recommendations, and this improvement was attributable to earlier diagnosis than would have been achieved without these clinics in 42% of cases. Including all patients examined, the proportion helped by early diagnosis at 18 to 30 months' follow-up was 23%. It is concluded that the offer of a routine examination to high risk groups is of benefit to old people and a form of medical practice which should be widely adopted.